(untitled) (Journal of Applied Oral Science, 2021)
Objective: To investigate the effects of intro-oral injection of parathyroid hormone (PTH) on tooth extraction wound healing in hyperglycemic rats. Methodology: 60 male Sprague-Dawley rats were randomly divided into the normal group (n=30) and DM group (n=30). Type 1 diabetes mellitus (DM) was induced by streptozotocin. After extracting the left first molar of all rats, each group was further divided into 3 subgroups (n=10 per subgroup), receiving the administration of intermittent PTH, continuous PTH and saline (control), respectively. The intermittent-PTH group received intra-oral injection of PTH three times per week for two weeks. A thermosensitive controlled-release hydrogel was synthesized for continuous-PTH administration. The serum chemistry was determined to evaluate the systemic condition. All animals were sacrificed after 14 days. Micro-computed tomography (Micro-CT) and histological analyses were used to evaluate the healing of extraction sockets. Results: The level of serum glucose in the DM groups was significantly higher than that in the non-DM groups (p<0.05); the level of serum calcium was similar in all groups (p>0.05). Micro-CT analysis showed that the DM group had a significantly lower alveolar bone trabecular number (Tb.N) and higher trabecular separation (Tb.Sp) than the normal group (p<0.05). The histological analyses showed that no significant difference in the amount of new bone (hard tissue) formation was found between the PTH and non-PTH groups (p>0.05). Conclusions: Bone formation in the extraction socket of the type 1 diabetic rats was reduced. PTH did not improve the healing of hard and soft tissues. The different PTH administration regimes (continuous vs. intermittent) had similar effect on tissue healing. These results demonstrated that the metabolic characteristics of the hyperglycemic rats produced a condition that was unable to respond to PTH treatment.